Hyperreactive platelet phenotypes: Relationship to altered serotonin transporter number, transport kinetics and intrinsic response to adrenergic co-stimulation - Berger, Jeffrey S.; Becker, Richard C.; Dentali, Francesco; Kuhn, Cynthia; Helms, Michael J.; Ortel, Thomas L.; Williams, Redford (Thrombosis and Haemostasis, 2013)
The mechanism underlying a hyperreactive platelet phenotype remains unknown. Since serotonin has been shown to influence platelet biology and atherothrombosis, we sought to investigate the association of platelet serotonin transporter number, binding affinity, and uptake kinetics with platelet aggregation. A total of 542 healthy volunteers had light transmittance platelet aggregometry measured in response to varying concentrations of epinephrine, serotonin, epinephrine plus serotonin, ADP and collagen. Transporter-dependent serotonin uptake rate was determined (Vmax), as were serotonin transporter number (Bmax) and binding affinity (Kd) using 3H paroxetine binding in a homologous displacement assay, nonlinear regression and validated algorithms for kinetic modelling. Stimulation with submaximal (2μM) epinephrine concentration elicited a distinct, bimodal pattern of platelet aggregation in this population. In contrast, subjects exhibited minimal aggregation in response to serotonin alone. Co-stimulation with submaximal epinephrine and serotonin induced platelet aggregation to a level beyond that observed with either agonist alone and maintained a bimodal response distribution. Subjects with heightened (>60%) platelet aggregation to both epinephrine alone and epinephrine plus serotonin exhibited increased platelet serotonin uptake, and transporter number and affinity. In a population of healthy subjects, co-stimulation with submaximal concentrations of epinephrine and serotonin identifies a subset of individuals with a hyperreactive platelet aggregation profile that is associated with changes in platelet serotonin function.
Keywords: Platelets; platelet activity; serotonin; epinephrine; transporter